LiAlO2 coated lithium-rich manganese-based material as well as preparation method and application thereof
By using the preparation method of LiAlO2 cladding in the lithium-rich manganese-based positive electrode material, the problem of degradation of material performance after pickling is solved, and the specific capacity, circulation performance and structural stability of the material are significantly improved, and damage to the material during compaction is avoided.
Patent Information
- Application Number
- CN202510117108.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lithium-rich manganese-based positive electrode materials have poor capacity, circulation performance and structural stability after pickling, and have too high specific surface area, resulting in a degradation of material performance.
The preparation method of LiAlO2 coated with lithium-rich manganese-based materials is adopted, and the residual alkali content is reduced through the pickling process, and an aluminum source and a second lithium salt are added on this basis for the second sintering to form a LiAlO2 coating layer to improve the structural stability and cyclic performance of the material.
The specific capacity, first circle efficiency and cycle stability of lithium-rich manganese-based materials are significantly improved, the dissolution and side reactions of nickel and manganese elements are reduced, the specific surface area is reduced, and the damage of the material during the compaction process is avoided.
Smart Images

Figure BDA0005258082800000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery materials, and in particular relates to a LiAlO2-coated lithium-rich manganese-based material and a preparation method and application thereof. Background Art
[0002] As a potential next-generation cathode material, lithium-rich manganese-based cathode materials are significantly superior to materials such as lithium iron phosphate and ternary materials because of their theoretical specific capacity of more than 250 mAh / g. In addition, lithium-rich manganese-based cathode materials also have the advantage of being relatively cheap. Further, by adopting a cobalt-free system, it can effectively reduce dependence on scarce resource cobalt. However, lithium-rich manganese-based cathode materials also have problems such as poor rate performance, low first-cycle coulomb efficiency, fast voltage decay, and insufficient cycle stability.
[0003] Through acid pickling treatment, the residual alkali content in the lithium-rich manganese-based positive electrode material can be effectively reduced and the first-cycle electrical performance of the material can be improved; however, acid pickling may cause lithium loss and transition metal dissolution, which will lead to the deterioration of the material's capacity, cycle performance and structural stability. At the same time, the excessively high specific surface area after acid pickling will cause the subsequent positive electrode material to be damaged during compaction. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the lithium-rich manganese-based materials in the prior art after pickling, such as poor capacity, cycle performance and structural stability, and excessive specific surface area, thereby providing a LiAlO2-coated lithium-rich manganese-based material and its preparation method and application.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The present invention provides a method for preparing a LiAlO2-coated lithium-rich manganese-based material, comprising the following steps:
[0007] (1) mixing a precursor and a first lithium salt, and performing a first sintering to obtain a sintered material;
[0008] (2) acid-washing the first sintered material, mixing it with an aluminum source and a second lithium salt, and performing a second sintering to obtain a LiAlO2-coated lithium-rich manganese-based material;
[0009] The pickling is performed using an organic acid solution.
[0010] In an optional embodiment, the aluminum source includes Al(OH)3, C9H 21 At least one of O3Al, Al2O3 and AlF3;
[0011] In an optional embodiment, the second lithium salt includes lithium hydroxide.
[0012] In an optional embodiment, in the step (2), after the sintered material is pickled, a pickled product is obtained, and based on the mass of the pickled product, the content of aluminum in the aluminum source is 2000-4000ppm; it should be noted that the content of aluminum in the aluminum source is the ratio of the mass of aluminum in the aluminum source to the mass of the pickled product;
[0013] In an optional embodiment, the molar ratio of the aluminum element in the aluminum source to the lithium element in the second lithium salt is (1.04-1.08):1.
[0014] In an optional embodiment, the second sintering is performed in an oxygen-containing atmosphere;
[0015] In an optional embodiment, the second sintering temperature is 500-700°C;
[0016] In an optional embodiment, the second sintering time is 4-6h;
[0017] In an optional embodiment, the heating rate of the second sintering is 2-4°C / min.
[0018] In an optional embodiment, the specific steps of pickling the burnt material include: placing the burnt material into an organic acid solution, stirring, filtering, and drying;
[0019] Preferably, the stirring time is 5-10 min;
[0020] Preferably, the stirring speed is 400-600 rpm;
[0021] Preferably, the filtration is suction filtration;
[0022] Preferably, the drying temperature is 100-120°C;
[0023] Preferably, the drying time is 2-4h;
[0024] Preferably, the filtration time is 15-20 min;
[0025] Preferably, the filtration pressure is -0.8 to -0.5 MPa.
[0026] In an optional embodiment, the mass ratio of the first burning material to the organic acid solution is 1:(0.5-2);
[0027] In an optional embodiment, the organic acid solution includes at least one of oxalic acid solution, citric acid solution, acetic acid solution, malonic acid solution and lactic acid solution;
[0028] In an optional embodiment, the concentration of the organic acid solution is 0.02-0.06 mol / L.
[0029] In an optional embodiment, in step (1), the precursor comprises nickel manganese hydroxide;
[0030] In an optional embodiment, the ratio of the total molar amount of nickel and manganese in the nickel manganese hydroxide to the molar amount of lithium in the first lithium salt is 1:(1.3-1.5);
[0031] In an optional embodiment, the first lithium salt includes at least one of lithium carbonate and lithium hydroxide;
[0032] In an optional embodiment, the first sintering is performed in an oxygen-containing atmosphere.
[0033] In an optional embodiment, the first sintering includes: first performing temperature-raising sintering, and then performing temperature-lowering sintering;
[0034] Preferably, the heating rate of sintering is 1-4°C / min;
[0035] Preferably, the temperature reduction sintering rate is 1-2°C / min;
[0036] Preferably, the specific steps of the temperature-raising sintering include: firstly raising the temperature to 650-750°C at 1-4°C / min and maintaining for 6-10h, then raising the temperature to 900-980°C at 1-4°C / min and maintaining for 8-12h;
[0037] Preferably, the specific steps of cooling and sintering include: cooling to 550-650° C. and maintaining for 0.5-2 h.
[0038] Preferably, the temperature reduction sintering further comprises: cooling to 550-650° C. and then naturally cooling to room temperature to obtain a sintered material;
[0039] The present invention also provides a LiAlO2-coated lithium-rich manganese-based material prepared by the above preparation method.
[0040] The present invention also provides an application of the LiAlO2-coated lithium-rich manganese-based material prepared by the above preparation method in a lithium-ion battery.
[0041] The technical solution of the present invention has the following advantages:
[0042] 1. The preparation method of the LiAlO2-coated lithium-rich manganese-based material provided by the present invention comprises the following steps: (1) mixing a precursor and a first lithium salt, and performing a first sintering to obtain a sinter; (2) pickling the sinter, mixing it with an aluminum source and a second lithium salt, and performing a second sintering to obtain a LiAlO2-coated lithium-rich manganese-based material; the pickling is performed using an organic acid solution. The present invention first uses a pickling process to pickle a sinter, effectively improving the first-cycle activation performance and first-cycle efficiency of the material while reducing residual alkali, and then adding an aluminum source and a second lithium salt to mix, and performing a second sintering to obtain a LiAlO2-coated lithium-rich manganese-based material. The charging specific capacity of the lithium-rich manganese-based material can be guaranteed by supplementing lithium, and the transformation from the layered phase to the rock salt phase can also be reduced; at the same time, the fast ion conductor LiAlO2 coating layer formed by the aluminum source and the second lithium salt can reduce the dissolution of nickel and manganese elements and the occurrence of side reactions, reduce gassing reactions, and improve the structural stability and cycle stability of the lithium-rich manganese-based material; the aluminum element can significantly improve the cycle performance of the lithium-rich manganese-based material. In addition, the LiAlO2 coating layer will also reduce the specific surface area of the lithium-rich manganese-based material to prevent it from being crushed during subsequent compaction. The present invention adopts a specific sequence of processes when preparing the lithium-rich manganese-based material, and uses an organic acid solution for pickling. On the basis of overcoming the defects of the existing pickling process, the material capacity, cycle performance and structural stability are improved, and the material has a suitable specific surface area.
[0043] 2. The preparation method of the LiAlO2-coated lithium-rich manganese-based material provided by the present invention adopts an organic acid solution for pickling. The organic acid remaining on the surface of the material generates a carbon-based gas and evaporates during the subsequent sintering, and there will be no adverse situation such as part of the inorganic acid generating solid by-products affecting the electrical properties. It also avoids the inorganic acid destroying the surface structure of the lithium-rich manganese-based material, causing the dissolution of nickel and manganese elements and the degradation of material performance.
[0044] The preferred aluminum sources of the present invention include Al(OH)3, C9H 21 O3Al, Al2O3 and AlF3, the by-products generated when the LiAlO2 coating layer is generated are all gases and can be directly removed. No solid by-products will remain on the surface of the lithium-rich manganese-based material to affect the performance. The present invention preferably takes the quality of the pickled product as the benchmark, and the content of aluminum in the aluminum source is 2000-4000ppm; adding aluminum within this range can further improve the specific capacity of the lithium-rich manganese-based material. DETAILED DESCRIPTION
[0045] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0047] Example 1
[0048] This embodiment provides a method for preparing a LiAlO2-coated lithium-rich manganese-based material, comprising the following steps:
[0049] (1) Ni 0.35 Mn 0.65 (OH)2 and lithium carbonate were mixed in a high-speed mixer, and in a muffle furnace, the temperature was raised from room temperature to 700°C at a heating rate of 3°C / min and then maintained for 8 hours, and then raised to 940°C at a heating rate of 3°C / min and then maintained for 10 hours; the temperature was lowered to 600°C at a cooling rate of 1°C / min and then maintained for 1 hour, and then naturally cooled to room temperature to obtain a burnt material; Ni 0.35 Mn 0.65 The ratio of the total molar amount of nickel and manganese in (OH)2 to the molar amount of lithium in lithium carbonate is 1:1.4;
[0050] (2) Pour the first burnt material into a 0.04 mol / L oxalic acid solution, stir at 500 rpm for 5 min, and then filter for 15 min at a filtration pressure of -0.8 MPa, and then place in a vacuum oven at 120°C for 2 h to obtain an acid-washed product; the mass ratio of the first burnt material to the oxalic acid solution is 1:1;
[0051] (3) The pickled product, Al(OH)3 and LiOH are mixed, and the temperature is raised from room temperature to 600°C at a rate of 3°C / min in an oxygen-containing atmosphere in a muffle furnace, then maintained at 600°C for 5 hours, and naturally cooled to room temperature to obtain a LiAlO2-coated lithium-rich manganese-based material; based on the mass of the pickled product, the content of aluminum in Al(OH)3 is 3000ppm; the molar ratio of aluminum in Al(OH)3 to lithium in LiOH is 1.06:1.
[0052] Example 2
[0053] The present embodiment provides a method for preparing a LiAlO2-coated lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (3), the molar ratio of the aluminum element in Al(OH)3 to the lithium element in LiOH is 1.04:1; instead of the molar ratio of the aluminum element in Al(OH)3 to the lithium element in LiOH in Example 1 being 1.06:1.
[0054] Example 3
[0055] The present embodiment provides a method for preparing a LiAlO2-coated lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (3), the molar ratio of the aluminum element in Al(OH)3 to the lithium element in LiOH is 1.08:1; instead of the molar ratio of the aluminum element in Al(OH)3 to the lithium element in LiOH of Example 1 being 1.06:1.
[0056] Example 4
[0057] This embodiment provides a preparation method of a LiAlO2-coated lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (3), the amount of aluminum element is 2000ppm based on the mass of the pickled product; instead of the method of Example 1 in which the amount of aluminum element is 3000ppm based on the mass of the pickled product.
[0058] Example 5
[0059] This embodiment provides a preparation method of a LiAlO2-coated lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (3), the amount of aluminum element is 4000ppm based on the mass of the pickled product; instead of the method of Example 1 in which the amount of aluminum element is 3000ppm based on the mass of the pickled product.
[0060] Example 6
[0061] This embodiment provides a method for preparing a LiAlO2-coated lithium-rich manganese-based material, comprising the following steps:
[0062] (1) Ni 0.35 Mn 0.65 (OH)2 and lithium hydroxide were mixed in a high-speed mixer, and in a muffle furnace, the temperature was raised from room temperature to 650°C at a heating rate of 1°C / min, and then kept for 10 hours, and then raised to 900°C at a heating rate of 1°C / min, and then kept for 12 hours; the temperature was lowered to 550°C at a cooling rate of 2°C / min, and then kept for 2 hours, and then naturally cooled to room temperature to obtain a burnt material; Ni 0.35 Mn 0.65 The ratio of the total molar amount of nickel and manganese in (OH)2 to the molar amount of lithium in lithium hydroxide is 1:1.3;
[0063] (2) Pour the burnt material into a 0.02 mol / L citric acid solution, stir at 400 rpm for 10 min, and then filter for 20 min at a filtration pressure of -0.5 MPa, and then place in a vacuum oven for drying at 100°C for 4 h to obtain an acid-washed product; the mass ratio of the burnt material to the citric acid solution is 1:2;
[0064] (3) The pickled product, C9H 21O3Al and LiOH were mixed, heated from room temperature to 700℃ at a rate of 2℃ / min in an oxygen-containing atmosphere in a muffle furnace, then kept at 700℃ for 4h, and cooled to room temperature to obtain LiAlO2-coated lithium-rich manganese-based material; based on the quality of the pickled product, C9H 21 The aluminum content in O3Al is 4000ppm; C9H 21 The molar ratio of aluminum in O3Al to lithium in LiOH is 1.04:1.
[0065] Comparative Example 1
[0066] This comparative example provides a method for preparing a lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (3), Al(OH) 3 and LiOH are not added.
[0067] Comparative Example 2
[0068] This comparative example provides a method for preparing a lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (3), Al(OH) 3 is not added.
[0069] Comparative Example 3
[0070] This comparative example provides a method for preparing a lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (3), LiOH is not added.
[0071] Comparative Example 4
[0072] This comparative example provides a method for preparing a lithium-rich manganese-based material. Compared with Example 1, the only difference is that in step (2), sulfuric acid solution is used in an equimolar amount to replace oxalic acid solution.
[0073] Comparative Example 5
[0074] This comparative example provides a method for preparing a lithium-rich manganese-based material, comprising the following steps:
[0075] (1) Ni 0.35 Mn 0.65 (OH)2, lithium carbonate and Al(OH)3 were mixed in a high-speed mixer, and heated from room temperature to 700°C at a heating rate of 3°C / min in an air atmosphere of a muffle furnace, and then kept for 8 hours, and then heated to 940°C at a heating rate of 3°C / min and kept for 10 hours; cooled to 600°C at a cooling rate of 1°C / min, and kept for 1 hour, and then naturally cooled to room temperature to obtain a sintered material; Ni 0.35 Mn 0.65 The ratio of the total molar amount of nickel and manganese in (OH)2 to the molar amount of lithium in lithium carbonate is 1:1.4; 0.35 Mn 0.65The total mass of nickel and manganese in (OH)2 is used as the basis, and the content of aluminum in Al(OH)3 is 3000ppm;
[0076] (2) Pour the first burnt material into a 0.04 mol / L oxalic acid solution, stir at 500 rpm for 5 min, and then filter for 15 min at a filtration pressure of -0.8 MPa, and then place in a vacuum oven at 120°C for 2 h to obtain an acid-washed product; the mass ratio of the first burnt material to the oxalic acid solution is 1:1;
[0077] (3) The acid-washed product and LiOH are mixed, and the temperature is raised from room temperature to 600° C. at a rate of 3° C. / min in an oxygen-containing atmosphere in a muffle furnace, then maintained at 600° C. for 5 hours, and naturally cooled to room temperature to obtain a LiAlO2-coated lithium-rich manganese-based material; the molar ratio of the aluminum element in Al(OH)3 in step (1) to the lithium element in LiOH in step (3) is 1.06:1.
[0078] Test Case
[0079] The performance tests of the lithium-rich manganese-based positive electrode materials prepared in the above examples and comparative examples are as follows:
[0080] Using N-methylpyrrolidone as a dispersant, a lithium-rich manganese-based positive electrode material, carbon black, and PVDF (polyvinylidene fluoride) are mixed in a mass ratio of 80:10:10 to prepare a positive electrode slurry, and the positive electrode slurry is evenly coated on a carbon-coated aluminum foil with a coating surface density of 3 cm2 / mg. The positive electrode is dried in an oven at 80°C for 2 h to obtain a positive electrode sheet; in an argon atmosphere in a glove box, a Celgard 2500 diaphragm and a lithium metal sheet are used as the negative electrode sheet, and the electrolyte is 1 mol / L (EC, EMC and DMC in a volume ratio of 1:1:1); a CR2032 button half-cell is assembled in the order of negative electrode sheet, electrolyte, diaphragm, electrolyte, and positive electrode sheet.
[0081] The performance of the battery prepared above and the lithium-rich manganese-based composite electrode of the comparative example were tested as follows:
[0082] (1) 0.2C discharge specific capacity test method: At 25°C, the battery is charged at 0.2C and discharged once at 0.2C. The results are shown in Table 1. The first efficiency calculation formula is as follows:
[0083] First efficiency = 100% × 1st discharge specific capacity / 1st charge specific capacity
[0084] (2) Cycle performance test method: At 25°C, the battery was charged at 0.2C, discharged once at 0.2C, and cycled 52 times. The results are shown in Table 1. The cycle performance calculation formula is as follows:
[0085] Cycle performance = 100% × 52th discharge specific capacity / 3rd discharge specific capacity
[0086] Table 1
[0087]
[0088]
[0089] The LiAlO2-coated lithium-rich manganese-based material prepared by the present invention has high specific capacity, high initial efficiency, and high cycle retention rate. It can be seen that the LiAlO2-coated lithium-rich manganese-based material prepared by the preparation method of the present invention has good structural stability and cycle stability; at the same time, the specific surface area is small, which avoids the positive electrode material from being destroyed during subsequent compaction.
[0090] From the comparison between Example 1 and Comparative Example 1, it can be seen that the 0.2C charge specific capacity, 0.2C discharge specific capacity, first efficiency and cycle retention rate of Comparative Example 1, which was directly sintered after pickling, were greatly reduced, indicating that the capacity, cycle stability and structural stability of the lithium-rich manganese-based material after pickling were all deteriorated.
[0091] From the comparison between Example 1 and Comparative Examples 2-3, it can be seen that adding an aluminum source and a second lithium salt to sinter to obtain a LiAlO2-coated lithium-rich manganese-based material can significantly improve the material's specific capacity and cycle performance, and has better structural stability; in Comparative Example 2, which only supplements lithium without adding an aluminum source, the 0.2C discharge specific capacity, first efficiency and cycle performance are significantly reduced; in Comparative Example 3, which only uses an aluminum source for coating without supplementing lithium, the 0.2C charge specific capacity is further reduced.
[0092] From the comparison between Example 1 and Comparative Example 4, it can be seen that pickling with strong inorganic acid will destroy the surface structure of the lithium-rich manganese-based material, and nickel and manganese elements will be dissolved. At the same time, by-products will remain on the surface of the positive electrode material, and its capacity and cycle performance will be significantly reduced.
[0093] From the comparison between Example 1 and Comparative Example 5, it can be seen that the LiAlO2-coated lithium-rich manganese-based material prepared according to a specific sequence of processes has a suitable specific surface area, while also improving the capacity, cycle performance and structural stability of the material.
[0094] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a LiAlO2-coated lithium-rich manganese-based material, characterized in that: The steps include: (1) mixing a precursor and a first lithium salt, and performing a first sintering to obtain a sintered material; (2) acid-washing the first sintered material, mixing it with an aluminum source and a second lithium salt, and performing a second sintering to obtain a LiAlO2-coated lithium-rich manganese-based material; The pickling is performed using an organic acid solution.
2. The preparation method according to claim 1, characterized in that: The aluminum source includes Al(OH)3, C9H 21 At least one of O3Al, Al2O3 and AlF3; and / or, The second lithium salt includes lithium hydroxide.
3. The preparation method according to claim 1, characterized in that: In the step (2), the first sintered material is pickled to obtain a pickled product, and based on the mass of the pickled product, the content of aluminum in the aluminum source is 2000-4000 ppm; and / or, The molar ratio of the aluminum element in the aluminum source to the lithium element in the second lithium salt is (1.04-1.08):
1.
4. The preparation method according to claim 1, characterized in that: The second sintering is performed in an oxygen-containing atmosphere; and / or, The second sintering temperature is 500-700° C.; and / or, The second sintering time is 4-6 hours; and / or, The heating rate of the second sintering is 2-4°C / min.
5. The preparation method according to claim 1, characterized in that: The specific steps of pickling the burnt material include: placing the burnt material into an organic acid solution, stirring, filtering, and drying; Preferably, the stirring time is 5-10 min; Preferably, the stirring speed is 400-600 rpm; Preferably, the filtration is suction filtration; Preferably, the drying temperature is 100-120°C; Preferably, the drying time is 2-4h; Preferably, the filtration time is 15-20 min; Preferably, the filtration pressure is -0.8 to -0.5 MPa.
6. The preparation method according to claim 1 or 5, characterized in that: The mass ratio of the burning material to the organic acid solution is 1:(0.5-2); and / or, The organic acid solution comprises at least one of oxalic acid solution, citric acid solution, acetic acid solution, malonic acid solution and lactic acid solution; and / or, The concentration of the organic acid solution is 0.02-0.06 mol / L.
7. The preparation method according to claim 1, characterized in that: In the step (1), the precursor comprises nickel manganese hydroxide; and / or, The ratio of the total molar amount of nickel and manganese in the nickel manganese hydroxide to the molar amount of lithium in the first lithium salt is 1:(1.3-1.5); and / or, The first lithium salt comprises at least one of lithium carbonate and lithium hydroxide; and / or, The first sintering is performed in an oxygen-containing atmosphere.
8. The preparation method according to claim 1 or 7, characterized in that: The first sintering includes: firstly performing temperature-raising sintering, and then performing temperature-lowering sintering; Preferably, the heating rate of sintering is 1-4°C / min; Preferably, the temperature reduction sintering rate is 1-2°C / min; Preferably, the specific steps of the temperature-raising sintering include: firstly raising the temperature to 650-750°C at 1-4°C / min and maintaining for 6-10h, then raising the temperature to 900-980°C at 1-4°C / min and maintaining for 8-12h; Preferably, the specific steps of the temperature reduction sintering include: cooling to 550-650° C. and maintaining for 0.5-2 h.
9. The LiAlO2-coated lithium-rich manganese-based material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the LiAlO2-coated lithium-rich manganese-based material prepared by the preparation method according to any one of claims 1 to 8 in lithium-ion batteries.
Citation Information
Patent Citations
Modified lithium-rich manganese-based positive electrode material and preparation method thereof
CN113823786A
Composite modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN114784234A
Cathode active material and preparation method thereof
CN116093306A
Coated high-voltage lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN119092668A
Low-residual-alkali lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN119263362A
Cited By
Cathode material with gradient double-phase structure and preparation method and application thereof
CN120423610A
Modified lithium-rich manganese-based positive electrode active material, preparation and application thereof, and lithium ion battery
CN122246092A